'Nobody comes to help us': lived experiences and needs of older adults who lost their only child in China. Issue 1 (31st December 2023) - Ning, Ni; Peng, Chenyang; Qi, Meiling; Li, Xiaoping; Sun, Mei
ABSTRACT: Purpose: This qualitative study aimed to gather insights into the experiences of older adults after losing their only child and explore meaningful life needs as a basis for social interventions. Methods: We conducted individual face-to-face interviews with 29 participants from 10 communities in Changsha, Hunan Province, China. Interviews were transcribed verbatim and then analysed using the inductive category development of conventional content analysis. Results: The experience of losing an only child was devastating and linked with a helpless life in old age. The analysis generated the following three themes encompassing their lived experiences and needs: afraid of getting sick, lying on the edge of misery and surrounded by loneliness. Conclusions: Losing an only child triggered older adults' feelings of being misunderstood, disconnected and hopeless. They had an increased likelihood of lacking more on love and belonging, esteem and self-actualization needs than their physiologic and safety needs. Findings from our study will raise awareness on this vulnerable group and help design intervention programmes targeting the specific needs of this neglected segment of the population.